Pyelonephritis XI. Effect of Growth Phase of Streptococcus faecalis on Serum Susceptibility and Virulence - Guze, Lucien B. (1970)
Rapidly growing Streptococcus faecalis was found to be markedly susceptible to the bactericidal activity of normal rat and rabbit sera, whereas stationary-phase organisms were resistant. In contrast, human serum killed neither phase organism. Further, human serum was found to interfere with killing by rabbit serum. The serosusceptible, rapidly growing organisms were less virulent than the seroresistant, stationary-phase organisms. This was tested by production of pyelonephritis in the rat after intravenous inoculation of the organism. Renal bacterial content over a period of 4 weeks was significantly less in those animals which had received rapidly growing organisms.